Geastrum episcopale: A new noticeable species with red-violet exoperidium - Kuhar, F. (2009)
A new species, Geastrum episcopale, is described from Argentina. Detailed descriptions and illustrations of fresh and dry basidiomata are provided along with photographs of microscopic elements, such as spores, capillitium, calcium oxalate crystals, and exo- and endoperidium surfaces. This fungus is typical of the genus in its morphology and ecology but clearly differs from every known species. This species can be distinguished easily by the red-violet (to magenta) exoperidium and the lilac endoperidium. Specimens were collected on wet soil composed of a superficial layer of ca. 5 cm leaf litter and 15 cm of particulate and melanized lignocellulosic material (pH 6.5) under Eugenia uruguayensis and Nectandra sp. © 2009 by The Mycological Society of American.